Economic Empowerment Assistance for Mosque Based Communities in Mandailing Natal Regency - Esli Zuraidah Siregar; Nurharisyah Hasibuan; Magdalena Magdalena; Anas Habibi Ritonga; Masrul Efendi Umar Harahap; Aisyah Budi Harahap; Yuli Eviyanti; Hasanul Khuluk; Nurhasanah Hasibuan (CV. AFDIFAL MAJU BERKAH, 2025)
The mosque holds a strategic role in the life of Muslims, not only as a place of worship but also as a center for social activities and economic empowerment. This community service program aims to assist mosque administrators in developing their economic potential through entrepreneurship training and the establishment of micro-enterprise units within mosque communities. The activity was conducted in Mandailing Natal Regency using a participatory approach based on the real needs of congregants. The results show that the program succeeded in establishing a special division within the Mosque Prosperity Council (BKM) responsible for managing community economic empowerment initiatives. There was a noticeable improvement in the understanding and skills of mosque administrators regarding Islamic economic concepts, micro-enterprise management, and digital marketing. The program also encouraged greater initiative among mosque congregants to optimize local economic resources, as seen through the emergence of mosque-based economic activities such as entrepreneurship training, local product bazaars, and the development of congregation-based business groups. These findings demonstrate that mosques can function effectively as economic centers capable of improving community welfare when supported by professional management and active participation from congregants.